INDONESIAN INJUSTICE IN LAW ENFORCEMENT FOR THE PERSECUTION OF NOVEL BASWEDAN - Wandri Soleh Indrawan; Erliana Ermalindis Silly; Hernando Dihargo (FRASA: ENGLISH EDUCATION AND LITERATURE JOURNAL, 2020)
Indonesia is a state of law, where crime must have sanctions, and the number of sanctions is inaccordance with the crimes committed. then what about the case of the persecution of pouringhard water on Baswedan's novel, which is controversial because it is considered ambiguous. (1)What causes controversy? (2) What facts are there in the Baswedan Novel case (3) what does theBaswedan Novel think about this case?.The purpose of this study is to find out what causes thecontroversy in the novel case as well as the evidence that is in the case of the novel and theresponse of Novel Baswedan about this case